An Exploration of Factors Influencing Oversharing on Facebook Groups (Journal of The Colloquium for Information Systems Security Education, 2024)
Social media usage is extremely prevalent and so is the oversharing of personal information online. This paper aims to examine the factors that influence information disclosure on Facebook and how participation in groups may affect sharing behaviors. Groups can provide a more intimate and supportive environment, which may lead to excessive information sharing. An online survey was conducted on Amazon’s Mechanical Turk platform with 373 accepted responses from self-reported Facebook users. The data was analyzed to determine which demographic and personality factors are correlated with oversharing behaviors on user profiles and within Facebook groups. This work has implications for understanding how individuals seek support online and what information they feel comfortable disclosing. Oversharing may increase user feelings of social support but also may make users vulnerable to cyberbullying and social engineering attacks.
Keywords: oversharing; information disclosure; social media; Facebook; social engineering